Transcriptome Sequencing and Bioinformatics Analysis of Ovarian Tissues from Pomacea canaliculata in Guangdong and Hunan - Liu, Jing; Li, Jian; Wang, Zhi; Yang, Hua (Mediators of Inflammation, 2022)
In this study, the fecundity of Pomacea canaliculata was studied by collecting egg masses from Guangdong and Hunan using field egg collection and indoor propagation. Through high-throughput RNA sequencing (RNA-seq), we analyzed the ovarian tissue of the snails in Guangdong (G_O) and those in Hunan (H_O) using comparative analysis of transcription. Moreover, we used bioinformatics methods to screen the key pathways and genes that affect the fecundity of snails from the two locations. Results. The results showed that the absolute fecundity and weight-relative fecundity of Pomacea canaliculata in Guangdong were significantly higher than those in Hunan. We found 1,546 differential genes through differential gene screening (528 genes upregulated in snails from Guangdong and 1018 in snails from Hunan). The ribosomal signaling pathway and rpl23a, uba52 are critical pathways and essential genes that affect the fecundity of snails. Conclusions. The 27 differential genes in the ribosome signaling pathway, collected from H_O, were all downregulated. As a result, ovarian tissue protein synthesis is impaired, which is an important mechanism that affects snails’ ability to reproduce.